Windows 8.1 Bible - Boyce, Jim, 1958-; Shapiro, Jeffrey R.; Tidrow, Rob (Bible., 2014)
Windows 8.1 coverage that goes above and beyond all competitors? Serving as an evolutionary update to Windows 8, Windows 8.1 provides critical changes to parts of Windows 8, such as greater customization of the interface and boot operations, return of a 'start button' that reveals apps, greater integration between the two interfaces, and updates to apps. Weighing in at nearly 1000 pages, Windows 8.1 Bible provides deeper Windows insight than any other book on the market. It's valuable for both professionals needing a guide to the nooks and crannies of Windows and regular users want.